EXTENSIVE READING FOR TRANSLATION: ACQUIRING VOCABULARY FOR BETTER RENDITION - Mahardika, I Gusti Ngurah Agung Wijaya (Institut Hindu Dharma Negeri Denpasar, 2019)
Errors in translation stems from numerous sources, yet one of the most common sources of the errors is the lack of vocabulary mastery. Therefore, it is imperative for aspiring translators to increase their vocabulary mastery. This article proposed extensive reading through the implementation of book club in Translation class to increase students’ vocabulary. The rationale for the book club as well as the details of the implementation are discussed herein.